Improving The Performance Skills of Class XI Students at SMAS Tasik Raja Labuhan Batu Selatan in Matricks by Using Model Problem Based Learning - Makhsyari Zaharayu Harahap (Berpusi Publishing, 2023)
Student performance skills show the success of a learning process. To obtain improved performance skills, appropriate action is needed to overcome problems that cause low learning outcomes. This research aims to improve students' performance skills in matrix material using the Problem Based Learning model in class XI of SMAS Tasik Raja Labuhanbatu Selatan. This research is Classroom Action Research following the Kemmis & McTaggart cycle, each cycle consisting of four stages, namely plan, action, observation and reflection which are analyzed quantitatively. The subjects of this research were 30 class XI students at SMAS Tasik Raja Labuhanbatu Selatan. The results of this research are an increase in students' performance skills as shown by the average value of student learning outcomes in cycle I is 68.20 with classical completeness of 46.66% and the average value of student learning outcomes in cycle II is 86 .60 with a classical completion percentage of 90%.